2018
DOI: 10.1002/2017gl076472
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Meridional and Seasonal Radiative Forcing by Sulfate Aerosol Solar Geoengineering

Abstract: We study the possibility of designing solar radiation management schemes to achieve a desired meridional radiative forcing (RF) profile using a two‐dimensional chemistry‐transport‐aerosol model. Varying SO2 or H2SO4 injection latitude, altitude, and season, we compute RF response functions for a broad range of possible injection schemes, finding that linear combinations of these injection cases can roughly achieve RF profiles that have been proposed to accomplish various climate objectives. Globally averaged R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 45 publications
2
61
0
Order By: Relevance
“…Aerosols prescribed in the stratosphere can cause local warming in the stratosphere by absorbing near-IR and terrestrial radiation (Stenchikov et al, 1998;Ferraro et al, 2011). This warming can lead to changes in the amount of water vapor in the stratosphere (Dessler et al, 2013) and the amount of high clouds by changing the tropospheric stability (Kuebbeler et al, 2012;Visioni et al, 2018). Boucher et al (2017) has shown that these fast adjustment processes can influence the effective radiative forcing of the climate system for sulfate aerosol injections.…”
mentioning
confidence: 99%
“…Aerosols prescribed in the stratosphere can cause local warming in the stratosphere by absorbing near-IR and terrestrial radiation (Stenchikov et al, 1998;Ferraro et al, 2011). This warming can lead to changes in the amount of water vapor in the stratosphere (Dessler et al, 2013) and the amount of high clouds by changing the tropospheric stability (Kuebbeler et al, 2012;Visioni et al, 2018). Boucher et al (2017) has shown that these fast adjustment processes can influence the effective radiative forcing of the climate system for sulfate aerosol injections.…”
mentioning
confidence: 99%
“…Either scenario creates a serious tradeoff between operational efficiency and costs on the one hand, and purported 'secrecy' on the other. Less efficiency for direct SAI deployment above the equator (Dai et al 2018) implies substantially more deployed payload for the same climate impact. More payload requires more or larger aircraft and more flights, making the program more easily detectable.…”
Section: Further Discussionmentioning
confidence: 99%
“…This is no verdict as to these four latitudes being optimal or definitive. It is a statement that, if forced to choose today, these four latitudes appear like a good starting point for discussions , Dai et al 2018. Note that while SAI latitudes matter, longitudes appear not to, as injections at any one longitude mix rapidly to all others.…”
Section: Stratospheric Aerosol Deployment Scenariomentioning
confidence: 99%
“…[15][16][17][18][19][20] Typical average values of the neutral/ion ratio during daytime at mid-latitudes in the stratosphere is about 10 12 , and it is independent by the type of molecular species because cosmic rays ionize all neutral molecules in the stratosphere with a similar efficiency. [19] This low ion/neutral ratio can be counterbalanced by the fact that ion-molecule reactions are generally much faster than the neutral-neutral reactions (i. e. the neutral chemistry involved in the conversion of SO 2 into H 2 SO 4 takes approximately 30 days [21] ), and can heavily alter the total budget of important molecular species in the atmosphere. Hence, reactions involving the radical cation SO �þ 2 (all along the manuscript the radical symbol in SO �þ 2 will be omitted for the sake of simplicity), which can be produced in the stratosphere by ionizing radiation, should be considered in the chemistry models used when evaluating the climate impact of solar geoengineering involving sulfur dioxide as aerosol precursor.…”
Section: Introductionmentioning
confidence: 99%